The historicist city in the tropical climate: conflations of identity, sustainability, permeability and walkability - Jahn Kassim, Puteri Shireen; Abdul Majid, Noor Hanita; Mohd Nawawi, Norwina; Abdul Latip, Nurul Syala (2015)
The paper argues the position of the historicist city, which is defined as a city derived from principles of history and tradition yet which embody a framework of urban form and spatial structure evoking historical form and cultural rootedness while still achieving goals of green urbanism and the low carbon city framework and targets. It is highlighted that these have the potential of developing not only a vocabulary of facade design and urban form that combined functions of the modern world yet which can achieve ‘permeability’, walkability, bioclimatic urban strategies and pedestrian comfort. By enhancing a range of design vocabulary developed from an abstraction and interpretation of Malay vernacular architecture which can eventually evolve into an urban and facade grammar language that can adorn continuous facades and treatments of integrated continuous walkways and bioclimatic massing and treatments. The aim is to create a theoretical framework of the historicist city that derived from vernacular principles yet were not physically copying the vernacular; by discussing Modernist theories of the historicist city and conflating it with abstractions that can become a range of building massing, treatments and elements that can achieve both low energy buildings and low carbon targets while having cultural rootedness and climatic connections with maximum walkability in the city population.